2015
DOI: 10.1152/jn.00146.2015
|View full text |Cite
|
Sign up to set email alerts
|

Changes in motor unit behavior following isometric fatigue of the first dorsal interosseous muscle

Abstract: The neuromuscular strategies employed to compensate for fatigue-induced muscle force deficits are not clearly understood. This study utilizes surface electromyography (sEMG) together with recordings of a population of individual motor unit action potentials (MUAPs) to investigate potential compensatory alterations in motor unit (MU) behavior immediately following a sustained fatiguing contraction and after a recovery period. EMG activity was recorded during abduction of the first dorsal interosseous in 12 subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
40
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 51 publications
13
40
3
Order By: Relevance
“…It is know that shifts in median frequency of the EMG signal, towards low frequencies, provides an indirect measure of metabolic and ionic state of active muscles [42,43], and is related to reductions in the muscle fiber conduction velocity [44]. Our results indicate that EMGFmed returns to baseline levels 5 minutes after exercise with vascular occlusion carried out to failure.…”
Section: Median Frequency Of the Emg Signalmentioning
confidence: 55%
See 2 more Smart Citations
“…It is know that shifts in median frequency of the EMG signal, towards low frequencies, provides an indirect measure of metabolic and ionic state of active muscles [42,43], and is related to reductions in the muscle fiber conduction velocity [44]. Our results indicate that EMGFmed returns to baseline levels 5 minutes after exercise with vascular occlusion carried out to failure.…”
Section: Median Frequency Of the Emg Signalmentioning
confidence: 55%
“…McManus et al [44] demonstrated an increase in the amplitude of EMG signal over a period of recovery after exercise carried out to the task failure with free blood flow, indicating the recruitment of larger motor units to compensate for the force reduction capacity in fatigued muscle. In our study, however, this possible additional recruitment of motor units was not converted into an increase in force generation capacity in the PO condition, probably due to fatigue of the type I muscle fiber, since the oxygen availability was partially preserved in this condition.…”
Section: Emg Peakmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, unlike at higher contractile intensities, the opportunity for changes in recruitment and de-recruitment of MUs is much greater in fatiguing submaximal tasks, which can have an impact on discharge rates. However, relatively few studies have assessed concurrently the interaction between recruitment and rate coding during fatiguing tasks (61). Finally, interpretations of fatigue-related changes in MU output in many studies cited here have necessarily been directed by findings obtained from single MUs, but from a functional aspect the system utilizes groups of concurrently activated MUs.…”
Section: Changes In the Neuromuscular Pathway With Fatiguing Exercisementioning
confidence: 99%
“…; McManus et al. ). It has been suggested that grouping MU data in this way misrepresents MU firing behavior (De Luca and Contessa ; Hu et al.…”
Section: Introductionmentioning
confidence: 97%